Comparison of double-plate appliance and facemask therapy in treating class III malocclusions - Üçem, Tuba Tortop; Üçüncü, Neslihan; Yüksel, Sema (American journal of orthodontics and dentofacial orthopedics, 2004)
The aim of this study was to compare the effects of the double-plate appliance (DPA) and the facemask (FM) in treating skeletal Class III malocclusions. Data were based on the pretreatment and posttreatment lateral cephalograms of 28 subjects with skeletal and dental Class III malocclusions. In the first group (7 girls, 7 boys; mean age, 10 years 3 months), each subject wore a DPA with 2 Class III elastics, which exerted a force of 350-400 g day and night except for meals. In the second group (7 girls, 7 boys; mean age, 10 years 5 months), each subject wore a Delaire-type FM with a removable intraoral appliance with a total force of 600 g. The patients were instructed to wear the appliance approximately 16 hours a day. An untreated control group (6 girls, 8 boys; mean age, 9 years 8 months) was formed that matched the treatment groups according to sagittal skeletal and dental classifications. Thirteen angular and 14 linear measurements were evaluated. The increase in ANB angle and the decrease in maxillomandibular differential in the treated groups showed significant differences compared with the control group ( P < .05). The increases in ANB and SNA angles in the FM group were significantly greater than in the DPA group ( P < .05). The increases in lower facial height and Me-ANS in the FM group were significantly different compared with the other groups ( P < .05). The overjet increased significantly in both treatment groups ( P < .001), but, in the DPA group, overjet was significantly greater than in the FM group ( P < .05). Protrusion of the maxillary incisors and retrusion of the mandibular incisors in the DPA group showed significant differences compared with the other groups ( P < .05).